Electronic and Spatial Structures of Water-Soluble Dinitrosyl Iron Complexes with Thiol-Containing Ligands Underlying Their Ability to Act as Nitric Oxide and Nitrosonium Ion Donors. (14th February 2012) - Vanin, Anatoly F.; Burbaev, Dosymzhan Sh.
Abstract : The ability of mononuclear dinitrosyl iron commplexes (M-DNICs) with thiolate ligands to act as NO donors and to trigger S-nitrosation of thiols can be explain only in the paradigm of the model of the [Fe + (NO + )2 ] core (Fe(NO)2 7 according to the Enemark-Feltham classification). Similarly, the (RS − )2 Fe + (NO + )2 + structure describing the distribution of unpaired electron density in M-DNIC corresponds to the low-spin (S = 1 / 2 ) state with a d 7 electron configuration of the iron atom and predominant localization of the unpaired electron on MO(d z 2 ) and the square planar structure of M-DNIC. On the other side, the formation of molecular orbitals of M-DNIC including orbitals of the iron atom, thiolate and nitrosyl ligands results in a transfer of electron density from sulfur atoms to the iron atom and nitrosyl ligands. Under these conditions, the positive charge on the nitrosyl ligands diminishes appreciably, the interaction of the ligands with hydroxyl ions or with thiols slows down and the hydrolysis of nitrosyl ligands and the S-nitrosating effect of the latter are not manifested. Most probably, the S-nitrosating effect of nitrosyl ligands is a result of weak binding of thiolate ligands to the iron atom under conditions favoring destabilization of M-DNIC.